SELECTION OF INDICATORS OF QUALITY MANAGEMENT SYSTEM AND MARKETING ANALYSIS OF MANAGEMENT OF NON-MANUFACTURING ENTERPRISES (International Journal of Innovative Technologies in Economy, 2022)
In contrast to the study of marketing management in manufacturing enterprises, great attention is paid to the quality management system in non-manufacturing enterprises (trade and paid services, tourism and catering, transport and construction), taking into account the marketing approach. As an integral part of the management system of the enterprise, its system of marketing activities, from the point of view of quality management, requires the same approaches to the organization of the process as the system itself. Because if the same requirements are not applied to the quality management in each element of the system, it is difficult to organize a completely quality management process. Therefore, when analyzing marketing activities from the point of view of the quality of management, it is necessary to study the second approach. The first approach involves studying the marketing process as an integral part of enterprise quality management. The second approach envisages the study of the quality of the management of the marketing process itself, guided by the principles, methods, functions and approaches to the quality management of the enterprise as a whole. By studying quality management in the context of marketing activities, it can be defined as a system of methods, tools and types of activities aimed at meeting the quality requirements and expectations of the process itself and its products. For this reason, it is possible to note the quality management of the process itself and the quality management of the product of the process.